Functional & enhanced graphene/polyamide 6 composite fiber constructed by a facile and universal method. (August 2019) - Zhang, Yunhai; Lu, Yue; Yan, XiaoJie; Gao, WenSheng; Chen, HuQiang; Chen, Qinjia; Bai, YongXiao
Abstract: Demand for multifunctional and high-strength fiber has substantially increased in textile industry, biomedical, and biotechnological applications. In this study, an efficient and environment-friendly method was developed for functionalizing graphene through weak interaction and the construction of polyamide 6 composite functional fiber. With a loading of 0.5 wt% functionalized graphene oxide, the tensile strength reached 4.21 cN/dtex, and the tensile modulus reached 33.86 cN/dtex, indicating 31.6% and 33.6% enhancement, respectively. Moreover, the UV protection factor increased to more than 471, and the antibacterial property also increased to a certain level (antibacterial efficacy (AE)% >94%) with a low addition (0.9 wt%) of functionalized graphene oxide, indicating that the fabric can effectively prevent the encroachment of bacteria. These functionalization and composite preparation methods provide a convenient and scalable route to prepare graphene-based nanocomposite fiber with high strength and multifunctional properties. It has promising practical application in textile, biomedical, and biotechnological fields.